Observation Of Clay Settlement Of Consolidation In Petarukan District Pemalang Regency Stabilized By Using Salt (Nacl) - Anjasmoro, Joko Dwi; Rezeki, Ingrid Multi (FAKULTAS TEKNNIK UNIVERSITAS SWADAYA GUNUNG JATI, 2019)
Soil stability is an effort made to improve the properties of the origin of the soil, basically stabilization using salt has the same principle as stabilization using other chemicals. Based on the research on native soil combat, the value of 42.25% is categorized into soil types have high plasticity therefore the soil needs repair or stabilization.In this study chemical stabilization was carried out by adding ingredients to stability of salt (Nacl) with a percentage of 4% , 8%, and 12% of the weight of the sample. The research method used is divided into two, namely physical properties test consisting of water content test, density test, atterberg test and filter analysis test and mechanical properties test consisting of compacting test and consolidation test .The results of physical properties test showed that the greater the percentage of NaCl addition in water content, plastic limit, shrinkage limit increased while the specific gravity value, liquid limit, plasticity index and pass filter No. 200 decreased. While in the compaction test the weight value of the maximum dry volume increases and the optimum water content value decreases along with the percentage addition of NaCl. The maximum weight value of maximum dry volume is 1.675 gr / cm3 and the lowest optimum water content is 15.509% in mixed soil with the percentage of addition of 12% NaCl. Meanwhile the consolidation test results showed that the greater percentage percentage of NaCl consolidation coefficient (Cv) increases , while for the Cc index value and the consolidation decrease (Sc) decreases.Keywords : clay soil, Stablizing,Consolidation , salt (NaCl).